CULTURAL DEVELOPMENT OF INDIGENOUS MUSIC - Fozilov Qaxramon Madaminovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the history of the development of the culture of qomusi music.